GENERALIZED DERMATITIS IN A MIXED-BREED GERMAN SPITZ DOG - Pande Kadek Putra Indrayudha; Putu Devi Jayanti; Putu Ayu Sisyawati Putriningsih (Buletin Veteriner Udayana, 2025)
Dermatitis is inflammation of the skin that can be caused by several agents such as external irritants, burns, allergens, trauma, and infections (bacterial, viral, parasitic, fungal). This article aims to report the findings of cases of generalized dermatitis in dogs due to Sarcoptes scabiei infestation and Malassezia sp. Infection. The case is a 8 year old male dog with mixed breed German Spitz. The dog was reported experiencing severe pruritus with alopecia all over the body. Physical examination of the animal revealed hyperpigmentation, licenification, crusting, ulceration, scales, rancid and oily odor. The dog’s skin then was scrapped, cytology of impression smear preparations, and acetate tape. The examination results showed the presence of Sarcoptes scabiei mites and Malassesia sp. The animal then was diagnosed as generalised dermatitis due to these two agents. Complete blood count (CBC) was done and the result showed that the animal had hypochromic macrocytic anemia. Causative treatment is done with ivermectin injection on day-0 and day-14 and second drug is fluconazole PO with 24 hour intervals for 7 days. The dog also given a symptomatic therapy using shampoo with lime sulfur and salicilic acid, the dog bathed twice a week for two week and continued once a week for two weeks. Supportive therapy is carried out by administering multivitamins and ferrous fluconate once a day for seven days. Supportive therapy for hair and skin growth is given by fish oil once a day for seven days and continue with administration four times a day until hair growth improves. Therapy for 14 days gave quite good results, marked by a reduction in lesions on the animal's skin, although the dog had not fully recovered. To prevent re-infection, animal environmental sanitation needs to be considered.